The First WORKS Conference on Transformation of Work in a Global Knowledge Economy - Bechmann, Martin (2008)
The relationship between the changes of the global economy and individual working conditions formed the background of the first WORKS conference “The transformation of work in a global knowledge economy: towards a conceptual framework”, held in Chania, Greece from 21st – 22nd September, 2006 and attended by around 50 European researchers. Experts from academia and trade unions from all over the world were invited to give insights into their field of research, contributing to one of the main topics of the conference: (i) globalisation and organisational restructuring, (ii) workers’ organisation, the quality of working life and the gender dimension and (iii) global experiences and recommendations.